A randomized placebo-controlled trial of duloxetine in patients with major depressive disorder and associated painful physical symptoms - Gaynor, Paula J; Gopal, Murali; Zheng, Wei; Martinez, James M; Robinson, Michael J; Marangell, Lauren B (Current medical research and opinion, 2011)
Painful physical symptoms are common in patients with major depressive disorder (MDD) and may predict poorer treatment outcomes. Duloxetine has demonstrated efficacy in treating both MDD and certain other painful conditions. This randomized, double-blind clinical trial assessed the effects of duloxetine in patients with both MDD and MDD-associated physical pain. Participants were outpatient adults with current MDD (DSM-IV-TR criteria; Montgomery-Åsberg Depression Rating Scale [MADRS] total score ≥20) and at least moderate pain (Brief Pain Inventory Short Form [BPI] average pain rating ≥3) and with at least one prior episode of MDD. Patients received placebo (N = 266) or duloxetine (N = 262) 60 mg once daily. This trial is registered at clinicaltrials.gov (NCT01000805). Coprimary outcomes were MADRS total score (change from baseline at 8 weeks) and BPI average pain rating (overall main effect over 8 weeks). The Sheehan Disability Scale (SDS) global functional impairment score (change from baseline at 8 weeks) was used to assess functioning. Remission was defined as MADRS total score ≤12 at the 8-week endpoint. Changes were analyzed using mixed-effects model repeated measures (MMRM). Compared with placebo, duloxetine significantly improved the mean MADRS total score, BPI average pain rating, and SDS global functional impairment score (all p ≤ 0.05 for analyses described above). The remission rate was significantly greater with duloxetine compared with placebo (p = 0.001) and was greater for duloxetine-treated patients with ≥50% versus <50% improvement in BPI average pain score (p ≤ 0.001). Treatment emergent adverse events that occurred in at least 5% of duloxetine-treated patients and at twice the rate of placebo included nausea, somnolence, constipation, decreased appetite, and hyperhidrosis. Rates of discontinuation due to adverse events were greater for duloxetine than placebo (8.0% vs 3.4%, respectively; p = 0.024). This study did not address the effects of duloxetine on MDD and comorbid pain of a known origin. These results support the efficacy and tolerability of duloxetine in the treatment of depression and associated painful physical symptoms in patients with MDD and at least moderate MDD-associated pain.